2014
DOI: 10.5194/bg-11-1199-2014
|View full text |Cite
|
Sign up to set email alerts
|

Can the heterogeneity in stream dissolved organic carbon be explained by contributing landscape elements?

Abstract: Abstract. The controls on stream dissolved organic carbon (DOC) concentrations were investigated in a 68 km 2 catchment by applying a landscape-mixing model to test if downstream concentrations could be predicted from contributing landscape elements. The landscape-mixing model reproduced the DOC concentration well throughout the stream network during times of high and intermediate discharge.The landscape-mixing model approach is conceptually simple and easy to apply, requiring relatively few field measurements… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 55 publications
1
32
0
1
Order By: Relevance
“…This indicates that there was a change in the spatial structure of Q sp depending on the wetness state of the system. These results are analogous to other studies that have also revealed seasonal and wetness dependency of hydrological and biogeochemical processes (Grayson et al, 1997;Buffam et al, 2007;Payn et al, 2012;Ågren et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that there was a change in the spatial structure of Q sp depending on the wetness state of the system. These results are analogous to other studies that have also revealed seasonal and wetness dependency of hydrological and biogeochemical processes (Grayson et al, 1997;Buffam et al, 2007;Payn et al, 2012;Ågren et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The dominance of near-surface hydrological flow paths in such soils results in episodic transport of DOC to streams during storm events, that is highly nonlinear (Buffam et al 2007;Laudon et al 2011;Å gren et al 2014;. In many areas, increasing DOC in surface waters has been reported and variously ascribed to the effects of reduced acid precipitation, changes in land management, climate change and increased drought frequency (Laudon et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the DOC flux-runoff relationship for this site is very similar to what has been observed in agricultural watersheds in the U.S. at a range of scales, and for large watersheds globally ( Figure 5). While this study isolates the DOC flux from soil in a homogenous agricultural catchment, which is a poorly quantified flux in the context of watershed carbon budgets [Regnier et al, 2013], inputs from other land cover types and in-stream processing would be expected to alter this relationship at larger scales [Dalzell et al, 2011;Ågren et al, 2014;Vidon et al, 2014].…”
Section: Implications For Watershed Dom Dynamicsmentioning
confidence: 99%